University Students’ Attitudes towards Cell Phone Learning Environment - Muhanna, Wafa’ N.; Abu-Al-Sha’r, Awatif M. (International Journal of Interactive Mobile Technologies (iJIM), 2009)
This study aims at investigating Jordanian university undergraduate and graduate students’ attitudes towards the learning environment where cell phones are used as learning tools in classroom. To achieve this goal, the researchers distributed two questionnaires among two groups of two different levels of randomly chosen university students at the Faculty of Educational Sciences at Al-al-Bayt University. The first one addresses 30 undergraduate students, 12 male and 18 female. The other addresses 20 graduates, 7 male and 13 female. The study comprised two independent variables, level and gender, as covariates. The findings indicate that undergraduates are more favorable to cell phone environment than graduate students. The study also reveals that cell phone has more influence on male students than on female students.